The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10600-005-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Hydrolyzed Lignin from Cotton-Seed Husks by Hydrogen Peroxide

Abstract: 547.99.992The functional composition and structural porosity of hydrolyzed lignin from cotton-seed husks was altered by oxidation with hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results showed that the lignin degradation gradually decreased as the concentration of H 2 O 2 increased. These results are similar to previous studies with varying concentrations of H 2 O 2 [12] [14]. Lignin forms a protective shield around cellulose, guarding it from enzymatic action and at the same time increases the crystallinity of cellulose [15] [16].…”
Section: Peanut Hull-alkaline Pretreatment and Lignin Losssupporting
confidence: 91%
“…The results showed that the lignin degradation gradually decreased as the concentration of H 2 O 2 increased. These results are similar to previous studies with varying concentrations of H 2 O 2 [12] [14]. Lignin forms a protective shield around cellulose, guarding it from enzymatic action and at the same time increases the crystallinity of cellulose [15] [16].…”
Section: Peanut Hull-alkaline Pretreatment and Lignin Losssupporting
confidence: 91%
“…As an oxidant, it can also be used for oxidizing lignin to introduce carboxylate groups . A study on the oxidation of hydrolyzed nonwood lignin showed that hydrogen peroxide (H 2 O 2 ) treatment of lignin can increase its carboxylate group and thus its water solubility . In another report, the black liquor of Caribbean Pine wood species was oxidized with hydrogen peroxide in the presence of ferrous ion .…”
Section: Introductionmentioning
confidence: 99%
“…16 A study on the oxidation of hydrolyzed nonwood lignin showed that hydrogen peroxide (H 2 O 2 ) treatment of lignin can increase its carboxylate group and thus its water solubility. 17 In another report, the black liquor of Caribbean Pine wood species was oxidized with hydrogen peroxide in the presence of ferrous ion. 18 Since nonwood and wood species have different properties, the value-added products generated from these wood species would respond differently to chemical reactions.…”
Section: ■ Introductionmentioning
confidence: 99%